Development of a Dyspnea Management Behavior Scale for Thai Chronic Obstructive Pulmonary Disease Patients - Wongsaita, Naiyana; Thanasilp, Sureeporn; Preechawong, Sunida (Journal of Health Research, 2017)
Background: Dyspnea is the most common and severe symptom in patients with chronic obstructive pulmonary disease (COPD) associated with progressively decreased lung function. Assessment of dyspnea management behavior in COPD patients is therefore of great importance in clinical practice. However, no valid and reliable measure presently exists to assess such behavior in Thai COPD patients. The purpose of this study was to develop a dyspnea management behavior scale (DMBS) for use in the Thai COPD patient population. Methods: This study was guided by scale development procedures. Development of the DMBS involved four steps: first, generating an item pool; second, performing a content validity procedure; third, performing an item analysis procedure; and fourth, performing a construct validity procedure using exploratory factor analysis (EFA). A convenience sample of 100 COPD patients was recruited for scale validation. Results: The DMBS was produced as a self-reporting questionnaire, comprising 17 items and a five-point Likert scale. The scale was divided into two components: (1) management of dyspnea exacerbation and (2) prevention of induced dyspnea. Psychometric testing confirmed the content and construct validity, as well as the internal consistency of the instrument when used by Thai COPD patients, with a Cronbach’s alpha coefficient of 0.93. The results of EFA showed that the two components accounted for 48.95% of the variation, with Eigenvalues of 8.81 and 1.61. Conclusions: The findings of this study support the development of the DMBS for assessing the dyspnea management behavior of Thai COPD patients. Further research is needed to field-test the psychometric properties of the DMBS.